CircIFITM1/miR-802/Foxp1 Axis Participates in Proliferation and Invasion of Lovo Cells. (24th June 2022) - Wan, Yu; He, Jinhua; Han, Zeping; Wang, Shengbo; Zhao, Yingying; Zeng, Di; Tang, Ying; He, Yiwei; Zeng, Lishan
Abstract : Objective . To explore the role of circIFITM1 and its potential molecular mechanism in colon cancer. Methods . The circIFITM1 in human samples and cell lines of colon cancer was measured via RT-PCR. The cyclicity of circIFITM1 was confirmed by agarose gel electrophoresis and Sanger sequencing, and the stability of circIFITM1 was confirmed by actinomycin D assay. The proliferative and invasive ability was detected by the CCK-8 assay and Transwell assay, respectively. RNA pull-down assay confirmed a combination of circIFITM1 and miRNA. Dual-luciferase reporter gene was used to detect the direct relationship between miRNA and the target gene. Results . circIFITM1 originated from the maternal gene IFITM1and had high stability. It was resistant to processing by actinomycin D. Upregulating circIFITM1 facilitated the proliferation and invasion of Lovo cells, while interfering with circIFITM1 expression inhibited them. circIFITM1 interacted with miR-802, and miR-802 targeted the 3 ′ UTR of FOXP1. The overexpression of circIFITM1 downregulated miR-802 and upregulated FOXP1. Conclusion . circIFITM1 facilitates the proliferative and invasive abilities via miR-802/FOXP1 in Lovo cells.